ABSENCE OF SEASONAL EFFECT ON THE IMMUNOMODULATORY ACTION OF BRAZILIAN PROPOLIS ON NATURAL KILLER ACTIVITY - Sforcin, J. M. [UNESP]; Kaneno, R. [UNESP]; Funari, S. R. C. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2002)
Propolis, a beehive product widely used in folk medicine as an antiinflammatory agent, has been attracting researchers' attention to scientifically elucidate its biological properties and therapeutic activities. The aim of this paper was to study the possible effect of propolis on natural killer activity, since propolis immunomodulatory action has been suggested, especially on non-specific immunity. Propolis was produced by africanized honeybees (Apis mellifera L.), collected throughout a whole year, and pooled by season. Hydroalcoholic solutions of propolis were prepared with each pool and administered to rats by gavage over three days. Natural killer activity of non-adherent spleen cells was evaluated by the 51Cr-release cytotoxicity assay against Yac-1 target cells. Our results indicated that the natural killer activity was increased in spleen cells from propolis-treated animals. There were no significant differences related to the seasonal effect on the immunomodulatory action of propolis.
Keywords: propolis; season; immunomodulation; natural killer activity; cytotoxic assay